Studi Kesiapan Guru Melaksanakan Kurikulum 2013 dalam Pembelajaran Berbasis Tematik Integratif Kelas IV MI Ma’had Islam Kopeng - julrissani julrissani; Safikri Taufiqurrahman (MODELING: Jurnal Program Studi PGMI, 2021)
This study aims to 1) describe the readiness of the teacher in carrying out an integrative thematic learning process, 2) describe the implementation of learning using the scientific approach carried out by grade IV teachers at MI Ma'had Islam Kopeng, 3) describe the implementation of authentic assessment carried out by the teacher grade IV at MI Ma'had Islam Kopeng. This type of research is qualitative research. The research subjects in this study were fourth-grade teachers at MI Ma'had Islam Kopeng. This research's object was the teachers' readiness to implement thematic integrative learning at MI Ma'had Islam Kopeng. Methods of data collection through interview and observation methods. The technique of analyzing data through qualitative analysis with a flow method consisting of data reduction, data presentation and conclusion drawing. The results showed that grade IV teachers at MI Ma'had Islam Kopeng had understood the 2013 Curriculum and carried out integrative thematic learning with a scientific approach and carried out learning preparation by the systematics specified in the 2013 curriculum. Class teachers in conducting authentic assessments experienced several obstacles. that is, because of the large number of students who have to be assessed so that the assessment is not thorough and optimal, as well as the many types of assessments that must be carried out so that the teacher experiences difficulties in making the assessment.